FENOMENOLOGI SOSIAL LGBT DALAM PARADIGMA AGAMA - Gunawan Saleh; Muhammad Arif (Jurnal Riset Komunikasi (JURKOM), 2018)
The LGBT movement began in Western societies. The forerunner to the birth of this movement was the formation of the Gay Liberation Front (GLF) in London in 1970. The movement was inspired by previous liberation movement in the United States in 1969 which took place at the Stonewall. LGBT campaign focuses on the efforts of awareness to the lesbian, gay, bisexual, and transgender people and the general public that their behavior is not an aberration so they deserve the sexual rights as everyone else. Theological issues during this indeed become an important point in the debate over homosexuality and LGBT in General. This research aims to know the LGBT within the paradigm of religion and social impact through social phenomenology study with a qualitative approach. This approach is considered able to reveal in depth. From the results of this research, it can be concluded that all religions (Islam, Christianity, Hinduism, and Buddhism) looked at LGBT is sexual behavior which is deviant and unacceptable by all existing religions, especially in Indonesia. It is also a social impact with an LGBT sexual behavior as a distorted structure will impact the community. Then it will also be damaging to the process of regeneration and descent so that the impact on the quality of human resources in the future.